2021
DOI: 10.1016/j.ijimpeng.2020.103738
|View full text |Cite
|
Sign up to set email alerts
|

Crashworthiness of poplar wood veneer tubes

Abstract: This work studies the potential of using wooden tubes for crash applications. The tubes were made from 1 mm thick "I214" poplar veneers, according to different stacking sequences. Four configurations were characterized under static crushing (5 mm/min) and the one that performed best ([90/04/90]) was chosen to undergo dynamic tests under a drop weight tower (5.7 m/s). This configuration presents significant energy absorption performance in static (31.6 J / g) and in dynamic (28.5 J / g) crushing for a material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Furthermore, recent research indicates that LVL exhibits noteworthy mechanical potential for applications involving crash and impact scenarios (Susainathan et al 2019;Guélou et al 2021aGuélou et al , b, 2022b. However, plywood, laminated veneer lumber (LVL) and, more generally, wood plies are heterogeneous, which leads to dispersion and a certain variability in mechanical properties (Guélou et al 2021b). It is therefore essential to analyse them in detail to consider their use as a structural material in transport, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent research indicates that LVL exhibits noteworthy mechanical potential for applications involving crash and impact scenarios (Susainathan et al 2019;Guélou et al 2021aGuélou et al , b, 2022b. However, plywood, laminated veneer lumber (LVL) and, more generally, wood plies are heterogeneous, which leads to dispersion and a certain variability in mechanical properties (Guélou et al 2021b). It is therefore essential to analyse them in detail to consider their use as a structural material in transport, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fastgrowing and high yielding presents advantages in short-rotation, but these attributes are traditionally assumed to come at the price of lower wood quality (Barnett and Jeronimidis 2003). Poplar wood has a relatively low density and strength (Xi et al 2009), but it is good at machining, bonding, and finishing properties, making it well-suited for producing veneers and veneer-related construction materials (Guélou et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hartig et al (2018) performed research on the lateral vehicle impact equipped with beech and a fiber glass reinforced beech tube. A more recent study by Guélou et al (2021) reported the potential use of tubes made of poplar veneer for crash applications and their peculiar energy absorption potential. The present study is based on a patent related to an additive manufacturing process that consists of rolling and gluing green veneers to form cylindrical tubes (Pommier et al 2017).…”
Section: Introductionmentioning
confidence: 99%